Hubungan Penyesuaian Diri di Perguruan Tinggi dengan Indeks Prestasi Kumulatif Mahasiswa Bimbingan dan Konseling FKIP Universitas Sriwijaya - Puriani, Risma Anita (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2017)
This study was based on the phenomenon of the students who still got lower grade point average. Those were thought to give the effect to the students’ grade point average. The objective of this study was to find out the correlation between self confidence in college with GPA (Grade Point Average) either individually or together. In the field, students’ self confidence were categorised as very good, good,fair, poor, and very poor. This quantitative research used ex post facto approach. The subjects of the study were the students of Guidance and Counseling, Faculty of Teacher Training and Education, Sriwijaya University, with total population 145 students and samples 105 students. Sampling technique used Proportional Random Sampling. Instruments in this study was a questionnaire enclosed using Likertscale which has been in the validity and realibility. Statistical data analysis techniques used Pearson Product Moment Correlation and double regression used Statistical Product Service Solution (SPSS) version 17.00. Based on the results of the study revealed there was a significant correlation between self confidence and GPA.